If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2y = 20whats Solving 9x + -2y = 20ahstw Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 9x + -2y + 2y = 20ahstw + 2y Combine like terms: -2y + 2y = 0 9x + 0 = 20ahstw + 2y 9x = 20ahstw + 2y Divide each side by '9'. x = 2.222222222ahstw + 0.2222222222y Simplifying x = 2.222222222ahstw + 0.2222222222y
| 2abc= | | 6n^3-5n^2-56n=0 | | 14=x(5x-3) | | 72=x(2x-7) | | 3x-2y+z=19 | | 110=x*0.81 | | 3t^2-8t=16 | | 9x-2y=20whatsy | | 45=x+3+x+5+x^2-3x+4x-3 | | 4-3=-26 | | 17-56=10-63 | | P=8x-4y | | 2x+y+3z=8 | | 1.5x+1.55=2.1 | | -26=4-3y | | y=x-(x*0.27)+(x*0.09) | | ln(2x)-5ln(x)=0 | | 7n+9=2.5n | | 3y+5z=99 | | 1x+3y+5z=100 | | 2x+3y+z=11 | | 9-4(2y-1)=45 | | r^4-6r^2+9=0 | | 12x^3-24x^2+96x+64=0 | | 42a^2-22a+10= | | 3x^2-10x-13= | | 14x(10x+7)=93 | | (n-7)(n-6)(n-5)=336 | | 5-3x+9=x+30+3x+5 | | 4(-x+5x)+3x= | | a+a=15 | | 2x+75y^2=13 |